2022
DOI: 10.4103/tcmj.tcmj_257_21
|View full text |Cite
|
Sign up to set email alerts
|

Emphysematous pyelonephritis

Abstract: A BSTRACT Urinary tract infections are commonly encountered and managed worldwide, and emphysematous pyelonephritis (EPN) is among the most serious types of urinary tract infections. EPN is an acute necrotizing infection of the kidney, often associated with high rates of renal loss and mortality. The symptoms of EPN infection can be nonspecific, but the clinical triad of fever, flank pain, and nausea represent the most common presentations. The diagnosis and classification are performe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
22
0
4

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 43 publications
0
22
0
4
Order By: Relevance
“…Outside of the head and neck, emphysematous infections of the abdomen and pelvis carry a high risk of mortality, between 10% and 50%. 6 , 7 , 8 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Outside of the head and neck, emphysematous infections of the abdomen and pelvis carry a high risk of mortality, between 10% and 50%. 6 , 7 , 8 …”
Section: Discussionmentioning
confidence: 99%
“…The most common organisms involved are Escherichia coli, Klebsiella pneumoniae , Proteus mirabilis , Clostridium perfringens , and S taphylococcus aureus . 5 , 6 , 7 , 8 Cases of emphysematous infections due to Candida albicans and Pseudomonas aeruginosa have also been reported. 8 , 9 , 10 , 11 , 12 Patients with poorly controlled diabetes and immunocompromised patients are at higher risk but many cases occur in immunocompetent individuals.…”
Section: Introductionmentioning
confidence: 99%
“…Emphysematous pyelonephritis (EPN) is a serious kidney infection characterized by acute necrotizing infection in the renal tissue and nearby structures [ 3 ]. EPN infection can have nonspecific symptoms, but the most common clinical presentation includes a triad of fever, flank pain, and nausea [ 3 ].…”
Section: Discussionmentioning
confidence: 99%
“…Emphysematous pyelonephritis (EPN) is a serious kidney infection characterized by acute necrotizing infection in the renal tissue and nearby structures [ 3 ]. EPN infection can have nonspecific symptoms, but the most common clinical presentation includes a triad of fever, flank pain, and nausea [ 3 ]. Blood test abnormalities often seen in EPN patients include leukocytosis, thrombocytopenia, elevated creatinine levels, high C-reactive protein levels, or hypoalbuminemia [ 3 ].…”
Section: Discussionmentioning
confidence: 99%
“…For patients with poorly controlled EPN, especially those with Grade 3 or Grade 4 severity, subsequent nephrectomy may still be necessary if medical therapy and PCD prove ineffective. 5 The prognosis of EPN is influenced by various factors. Numerous studies have demonstrated that certain initial presentations are significantly associated with mortality.…”
mentioning
confidence: 99%